Polyarticular Septic Arthritis Caused by Haemophilus influenzae Serotype f in an 8-Month-Old Immunocompetent Infant: A Case Report and Review of the Literature - Raheel Ahmed Ali; Sheldon L. Kaplan; Scott B. Rosenfeld (Case Reports in Orthopedics)
Background. The standard use of vaccinations against pathogens has resulted in a decreased incidence of musculoskeletal infections caused by these previously common bacterial pathogens. Consequently, the incidence of infections caused by atypical bacteria is rising. This report presents a case of septic arthritis caused by non-type b H. influenzae in a pediatric patient. Methods. We report a case of an infant with polyarticular septic arthritis caused by H. influenzae serotype f. A literature review was conducted with the inclusion criteria of case reports and studies published between 2004 and 2013 addressing musculoskeletal H. influenzae infections. Results. An 8-month-old female presented with pain and swelling in her right ankle and left elbow. The patient was diagnosed with septic arthritis and underwent incision and drainage. Wound and blood cultures were positive for Haemophilus influenzae serotype f. In addition to treatment with IV antibiotics, the patient underwent immunocompetency studies, which were normal. Subsequent follow-up revealed eradication of the infection. Conclusions. Haemophilus influenzae non-type b may cause serious invasive infections such as sepsis or septic arthritis in children with or without predisposing factors such as immunodeficiency or asplenia. Optimal treatment includes surgical management, culture driven IV antibiotics, and an immunologic workup.